2004
DOI: 10.1255/jnirs.414
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Colour and pH in Grapes Using a Diode Array Spectrophotometer (400–1100 nm)

Abstract: One hundred and twenty thawed samples of homogenised and whole frozen grape berries were analysed using a diode array spectrophotometer (400-1100 nm) (CORONA 45VISNIR, Carl Zeiss, Germany). The spectra and the analytical data were used to develop partial least squares calibrations to predict colour and pH in both presentation modes to the instrument. The visible (vis: 400-700 nm), near infrared (NIR: 700-1100 nm) and vis + NIR (400-1100 nm) regions were used to perform the calibrations. Cross validation models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 21 publications
(41 reference statements)
4
60
2
Order By: Relevance
“…However, nowadays, this large-scale analysis is very difficult to do, or even impossible, because the conventional methods for chemical analysis of grapes are invasive, costly and time-consuming since these methods require sample preparation. The present study describes a solution to this problem: a recent methodology (Cozzolino et al, 2004(Cozzolino et al, , 2006 which combines portable spectroscopy and machine learning algorithms to determine, without sample preparation, some grape enological parameters for estimating grape maturity, such as pH, sugars and anthocyanin content.…”
Section: Introductionmentioning
confidence: 99%
“…However, nowadays, this large-scale analysis is very difficult to do, or even impossible, because the conventional methods for chemical analysis of grapes are invasive, costly and time-consuming since these methods require sample preparation. The present study describes a solution to this problem: a recent methodology (Cozzolino et al, 2004(Cozzolino et al, , 2006 which combines portable spectroscopy and machine learning algorithms to determine, without sample preparation, some grape enological parameters for estimating grape maturity, such as pH, sugars and anthocyanin content.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is common for the evaluation of quality of beverages by measuring the SSC and pH content in the beverage industry. The lack of a simple, reliable, and nondestructive method for the determination of chemical composition in beverage has been one of the main obstacles for the development of fast quality control in both the food industry and commercial grade (Cozzolino et al 2004;Behrendt et al 2002). In recent years, the spectroscopic technique has been frequently adapted for the determination of the chemical composition of food (Osborne and Fearn 1986).…”
Section: Introductionmentioning
confidence: 99%
“…No separation or clustering was observed between samples according to the time of heating. The highest eigenvectors were observed in the VIS region around 576 nm related to anthocyanins and at 670 nm and 680 nm related to chlorophylls [9,[13][14][15][16]. This indicates that microwaving might have an effect on the absorbance of some of the grape pigments.…”
Section: Physical Effectsmentioning
confidence: 89%
“…Previous studies have reported the effect of homogenisation and storage on both chemical composition and near infrared (NIR) spectra of red grapes [9,[12][13][14][15][16]. However, no reports have been found on the effect of microwaving on chemical composition of red grapes.…”
Section: Introductionmentioning
confidence: 99%